ANALYSIS OF FLEXIBLE POWER GENERATION AND REPOWERING SMALL MODULAR REACTOR ON SMALL-SCALE COAL-FIRED POWER PLANT - Adytia Putra, Ryan
This study examines the application of Flexible Power Generation (FPG) and repowering using Small Modular Reactors (SMR) in a Small-Scale Coal-Fired Power Plant (SSCFPP) to enhance operational flexibility and energy efficiency. FPG with biomass co-firing allows the plant to operate more efficiently at low capacity and become more responsive to fluctuations in power demand. At 45% load capacity, an efficiency of 27.70% was achieved, which is 1.3% higher than the existing model at 48% load operation. However, the co-firing operation increases the risk of slagging and fouling in the boiler, which can reduce efficiency and accelerate equipment degradation. Meanwhile, repowering with SMR improves the reliability of SSCFPP, reduces dependence on coal, and lowers CO? emissions. SMR also offers a smaller modular design, allowing for faster installation and lower construction costs. Based on the economic analysis, a net income of USD 43.8 million per year with a payback period of 16 years was obtained. This study shows that the combination of FPG with biomass co-firing and repowering with SMR can enhance the flexibility and operational sustainability of SSCFPP, although challenges related to slagging, fouling, and economic analysis need to be addressed for optimal implementation.